Prevalence of Diabetes, Hypertension and Obesity among Doctors and Nurses in Universal College of Medical Sciences, Bhairahawa, Nepal - Shah, Sudhir Kumar (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Hypertension (HTN) and diabetes mellitus (DM) both are rapidly emerging as public health problems in developing countries. Hypertension is the leading cause of cardiovascular disease and is also a major cause of disability, causing an estimated 13% of all deaths in the world. Diabetes mellitus, hypertension and obesity are very strongly associated with cardiovascular diseases all over the world. MATERIAL AND METHODS A cross sectional study was done among the doctors and nurse working in UCMS teaching hospital from Sep, 2020 to Feb, 2021. A total of 138 doctors and nurses were selected using a simple random sampling technique. Descriptive statistical analysis was used for the calculation of central tendency and dispersion measures. Chi- Square test was applied for categorical predictors and P value of less than 0.05 was considered as statistically signiﬁcant. RESULTS Doctors formed 47 % while nurses formed 53% of the study population. Prevalence of hypertension was found to be 18% among doctors and 7% among nurses. Prevalence of diabetes mellitus was found to be 6% among doctors and 8% among nurses. Prevalence of obesity was found to be 47% among doctors and 48% among nurses. The overall prevalence of hypertension, diabetes mellitus and obesity was the order of 25%, 14% and 95% respectively. CONCLUSION These ﬁndings provide important information on prevalence of hypertension, diabetes mellitus and obesity along with its associ- ated risk factors among doctors and nurses working in UCMS teaching hospital. Preventive health measures like low fat diet, physical activity, cessation of smoking, control of alcohol and various strategies are needed for the prevention of these cardio-vascular disease among doctors and nurses working at UCMS teaching hospital.